2012
DOI: 10.4103/2229-516x.106353
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic changes following neoadjuvant chemotherapy in various malignancies

Abstract: Background:Various histopathological changes have been observed following neoadjuvant chemotherapy in individual tumors in the literature.Aims and Objectives:To observe histopathologic changes seen after neoadjuvant chemotherapy in breast malignancies, squamous cell carcinomas, adenocarcinomas, and Wilms′ tumor using breast cancer predominantly as the model.Materials and Methods:The present prospective study was carried out on 60 patients including 40 patients with carcinoma breast and 20 patients with other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 11 publications
1
44
1
1
Order By: Relevance
“…Differentiation after DNA-damaging therapies has been observed in diverse cancers [42, 43]. We show that the combination of genotoxic stress, functional p53 and impaired apoptosis is sufficient to induce abundant differentiation, as xRT provoked neural differentiation in tumors with intact p53 and Bax deletion.…”
Section: Discussionmentioning
confidence: 78%
“…Differentiation after DNA-damaging therapies has been observed in diverse cancers [42, 43]. We show that the combination of genotoxic stress, functional p53 and impaired apoptosis is sufficient to induce abundant differentiation, as xRT provoked neural differentiation in tumors with intact p53 and Bax deletion.…”
Section: Discussionmentioning
confidence: 78%
“…More detectable changes in mean values of MBF, SI parametric maps were observed at week 8. These findings suggests that development of response in tumor cells is a gradual process which initially affects tissue micro-structure arrangement such as the spacing between lobules and later affects macro-structure such as lobule size, shape and their elastic properties and finally replaced with collagen and fibrotic deposition which reflect longer-term results of cell death process [ 33 ]. Ali et al [ 16 ] reported R and NR classification with the sensitivity 100% and specificity 100% early after NAC using combined mean QUS values and texture features.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using SHG imaging, Wu et al demonstrated on ex vivo samples of patients' breast tissue that tumors underwent a fibrosis reaction, in which the tumor cells were replaced by collagen fibers post-chemotherapy with docetaxel, doxorubicin, and cyclophosphamide (16). Sethi et al observed collagenization in the breast tumor stroma following neoadjuvant chemotherapy (cyclophosphamide, doxorubicin, and 5-fluorouracil, or cyclophosphamide, epirubicin, and 5-fluorouracil), that significantly correlated to the pathological response and grade of tumor regression (31). Tumor replacement by loose fibrosis after neoadjuvant chemotherapy (cyclophosphamide, methotrexate, fluouracile) was identified in breast cancer in (32).…”
Section: Discussionmentioning
confidence: 99%